Salmonella Infantis, a Potential Human Pathogen has an Association with Table Eggs - Samiullah, Samiullah (International Journal of Poultry Science, 2013)
Food borne Salmonellosis in human is mainly caused by the consumption of contaminated eggs and other poultry products. Trans-shell route is considered the underlying phenomena leading to the production of Salmonella Infantis contaminated eggs. Salmonella Infantis comes in the top 10 human pathogenic Salmonella serovars, been isolated from human and poultry from diverse group of countries in patients linked to contaminated food. Majority of the Salmonella cases are sporadic, outbreaks occur frequently with a direct or indirect link to contaminated food especially poultry. This review has mainly highlighted the factors affecting Salmonella transmission with a special emphasis on hen eggshell quality.